Нескучный сад Бориса Пастернака: между двумя поэтическими книгами (Поэзия и ее „определения") - Абрамова, Ксения (Studia Rossica Posnaniensia, 2019)
The article analyzes Boris Pasternak’s Poeziya (Poetry) from the cycle Neskuchny Sad. The cycle is the kind of a link between two poetic books of Boris Pasternak: Sestra moya – zhizn’ (My sister – Life) and Temy i variatsii (Themes and variations). We dwell in detail on the comparison of this text with the poem Opredeleniye poezii (Definition of poetry) from the book Sestra moya – zhizn’. We are mainly interested in the asemantic level of texts – their sound and rhythmic organization. The analyzed structure allows us to trace the dynamics of the images and the changes that took place in the poetic style of Boris Pasternak in the 1920s.